Revised version of retracted article: The development and preliminary validation of a social-emotional skills assessment instrument for Estonian lower secondary school students - Einpaul, Piret; Leijen, Äli; Baucal, Aleksandar (Psihološka istraživanja, 2025)
Given the necessity of comprehensive and psychometrically sound instruments to measure students’ social-emotional skills (SE skills) in school context and on a facet level, this study aimed to develop and evaluate a SE skills assessment instrument for lower secondary school students. The initial version of the instrument was developed based on the descriptions of SE skills from the frameworks by Primi et al. (2017) and the Organisation for Economic Co-operation and Development (OECD; Chernyshenko et al., 2018) and consisted of 48 items. A confirmatory factor analysis (CFA) was conducted with a sample of 204 students from Estonia and a 9-factor instrument with 34 items was refined. This model was confirmed with acceptable fitness by CFA with another sample of 521 students. Scalar measurement invariance was established between grade groups (grades 6 and 9). In conclusion, while the instrument allows assessing students’ SE skills in lower-secondary schools, further research is required.